Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1093/milmed/163.7.439
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Women's Health Care Needs on U.S. Navy Ships

Abstract: Authors alone are responsible for opinions expressed in the contribution and for its clearance through their federal health agency. If required. MILITARY MEDICINE, 163,7:439,1998 A Survey of Women's Health Care Needs on U.S. Navy Ships A total of 628 female and 526 male U.S. military personnel completed a health survey questionnaire at the completion of four shipboard deployments lasting 10 to 180 days (mean, 57 days). During deployment, women visited clinic (sick call) at significantly higher rates than me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Only 27% of the Sexual Health 8 women reported that a condom was always used. (Means-Markwell et al, 1998) Condom Use with High-Risk Populations…”
Section: Condom Usementioning
confidence: 99%
See 1 more Smart Citation
“…Only 27% of the Sexual Health 8 women reported that a condom was always used. (Means-Markwell et al, 1998) Condom Use with High-Risk Populations…”
Section: Condom Usementioning
confidence: 99%
“…(Malone et al, 1994;Means-Markwell et al, 1998) However, no published studies were found that addressed the sexual risk behavior, or rates of STI and unplanned pregnancies during post-Vietnam U.S. Army deployments.…”
Section: Introductionmentioning
confidence: 99%
“…15 A later study surveyed 628 female and 526 male sailors at the completion of four separate deployments lasting 10-180 days and found that women visited sick call 189/1000 per week vs. 117/1000 per week for men (a ratio of 1.61:1). 16 In the Perceptions of Wellness and Readiness study, questionnaire data was obtained from 9859 active duty shore based Marine Corps and Navy personnel. The study found that women tended to have higher rates of physical and mental illness, poorer perceptions of their health status and greater health care and medication use than their male counterparts.…”
Section: Health Care Usage Ratesmentioning
confidence: 99%
“…The most common gynecological visits were requests for contraceptive pills, vaginal discharge, menstrual cramps or abnormalities, and pregnancy checks. 16 A 1990 study by Hughey revealed 2.7 gynecological visits per female crewmember per year (excludes routine prenatal care), 8% of which required consultation to a specialist. 107 Nice and Hilton surveyed sick call visits on 23 ships in 1988-89 and found a gynecological visit rate of 1.2 per female crewmember per year.…”
Section: General Gynecological Needsmentioning
confidence: 99%